Position Statement: Models in Software and Systems Development - Mahr, Bernd (Electronic Communications of the EASST, 2010)
The development of software and systems is, by its very nature, highly depending on models. In the software and system’s design models play an important role, where they represent the constraining standards as well as the choices of ideas and perspectives applied in the systems modelling, implementation and technology. The general model of model-being, developed by the author, is briefly explained and is used to discuss model interconnections resulting from model compositions and metamodel applications. In this position statement it is claimed that the analysis of model interconnections, prerequisite to or underlying the software and systems design, should provide new insights into the designs architecture.